Performance test of pipe-shaped radiation shields for cryogenic interferometric gravitational wave detectors. (14th July 2015) - Sakakibara, Yusuke; Kimura, Nobuhiro; Akutsu, Tomotada; Suzuki, Toshikazu; Kuroda, Kazuaki
Abstract: One of the most important challenges in cryogenic interferometric gravitational wave detectors is to reduce the undesirable thermal radiation coming through holes in the radiation shield, which are necessary for the laser beam to pass through. For this purpose, pipe-shaped radiation shields called duct shields are used. Here, we have manufactured duct shields for KAGRA in Japan, one of the cryogenic interferometric gravitational wave detectors, and measured the thermal radiation coming through the duct shields. The measured result was found to be consistent with the calculation result that the duct shield can reduce the thermal radiation to less than 1%. This fact confirmed that the amount of thermal radiation coming through the duct shields was smaller than KAGRA's requirement.